SCN2A-Related Epilepsy: The Phenotypic Spectrum, Treatment and Prognosis - Zeng, Qi; Yang, Ying; Duan, Jing; Niu, Xueyang; Chen, Yi; Wang, Dan; Zhang, Jing; Chen, Jiaoyang; Yang, Xiaoling; Li, Jinliang; Yang, Zhixian; Jiang, Yuwu; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective: The aim of this study was to analyze the phenotypic spectrum, treatment and prognosis of 72 Chinese children with SCN2A variants. Methods: The SCN2A variants were detected by next-generation sequencing. All patients were followed up at a pediatric neurology clinic in our hospital or by telephone. Results: In 72 patients with SCN2A variants, the seizure onset age ranged from the first day of life to 2 years and 6 months. The epilepsy phenotypes included febrile seizures (plus)(n=2), benign (familial) infantile epilepsy(n=9), benign familial neonatal-infantile epilepsy(n=3), benign neonatal epilepsy(n=1), West syndrome(n=16), Ohtahara syndrome(n=15), epilepsy of infancy with migrating focal seizures (n=2), Dravet syndrome (n=1), early infantile epileptic encephalopathy (n=15), and unclassifiable developmental and epileptic encephalopathy (n=8). 79.1% (57/72) patients had varying degrees of developmental delay. All patients had abnormal MRI findings with developmental delay. 91.6% (55/60) patients with de novo SCN2A variants had development delay, while only 16.7% (2/12) patients with inherited SCN2A variants had abnormal development. 83.9% (26/31) SCN2A variants that were located in transmembrane regions of the protein were detected in patients with development delay. 69.2% (9/13) SCN2A variants detected in patients with normal development were located in the non-transmembrane regions. 54.2%（39/72）patients were seizure-free at a median age of 8 months. Oxcarbazepine has been used by 38 patients, and seizure-free was observed in 11 of them (11/38, 28.9%), while 6 patients had seizure worsening by oxcarbazepine. All 3 patients used oxcarbazepine and with seizure onset age ＞1 year presented seizure exacerbation after taking oxcarbazepine. Valproate has been used by 53 patients, seizure-free was observed in 22.6% (12/53) of them.